Adherence to guidelines on nutrition support during intensive treatment of acute myeloid leukemia patients: A nationwide comparison. (October 2020) - van Lieshout, Rianne; Tick, Lidwine W.; de Laat, Daphne; Custers, Stephanie; Dekker, Ingeborg M.; Douma, Madieke D.; Kalter, Doris; Kranenburg, Suzanne; van der Lee, Debbie; Rhoon-Bruijnzeel, Patricia; Schlösser, Ien; Somer, Maaike; et al.
Summary: Background & aims: The level of adherence to the updated guidelines of The European Societies for Clinical Nutrition and Metabolism (ESPEN) and for Blood and Marrow Transplantation (EBMT) on nutrition in intensively treated adult acute myeloid leukemia (AML) patients in clinical practice is unknown. The aim of this nationwide survey was to investigate ESPEN/EBMT nutritional guideline adherence during intensive AML treatment, variation in nutrition support practices among hospitals and whether these practices changed after guideline publication. Methods: All 22 Dutch hospitals providing (aftercare following) high-dose chemotherapy and/or hematopoietic stem cell transplantation for adult AML patients were surveyed on nutrition support practices during these intensive AML treatments. We used an online questionnaire in 2015 and semi-structured telephone interviews in 2018–2019. Both surveys were completed by registered dieticians and addressed the use of enteral (EN) and parenteral (PN) nutrition. The ESPEN/EBMT nutritional guideline adherence was investigated through the telephone interviews. Results: High-level ESPEN/EBMT guideline adherence and/or uniformity among hospitals regarding nutrition support practices during intensive AML treatment were observed for nutritional screening, -aims, safe food handling and exercise training. Adherence to ESPEN/EBMT recommendations that were not implemented into national guidelines, including nutritional assessment and use of medical nutrition, was poor. All hospitals assessed nutritional intake, -impact symptoms and body weight, but muscle mass, physical performance and degree of systemic inflammation were rarely and variably monitored. Although the number of hospitals using EN as first-choice nutritional intervention increased from 3 hospitals in 2015 to 8 in 2019, PN remained the preferred method of nutrition support. Furthermore, the timing of medical nutrition varied. Conclusions: Although the use of EN increased after publication of the updated ESPEN/EBMT nutritional guidelines, adherence to these standards was limited and there was heterogeneity in nutrition support practices during intensive AML treatment among hospitals. Incorporating international nutritional standards into national guidelines by nutrition expert groups immediately upon publication may improve adherence.